2019
DOI: 10.1002/jsfa.9812
|View full text |Cite
|
Sign up to set email alerts
|

Development, modification and characterization of new biodegradable film from basil seed (Ocimum basilicum L.) mucilage

Abstract: BACKGROUND: Biodegradable films from basil seed mucilage (BSM) were formed and modified with several di-carboxylic acid crosslinkers; i.e. tartaric acid (TA), malic acid (MA) and succinic acid (SA) with varying acidity and chemical structures, to enhance mechanical properties and water barrier ability. Basil seeds have a reasonable mucilage content and valuable properties; thus, it has the potential to develop valuable new biodegradable films. RESULT:We characterized BSM films with the three crosslinkers using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The obtained FTIR spectra were compatible with many studies on BSG-based edible lms [50,51]. When the spectra were examined, it was observed that the O-H stretch bands became sharper and shifted to lower wave numbers with increasing glycerol concentration.…”
Section: Ft-ir Spectroscopysupporting
confidence: 84%
“…The obtained FTIR spectra were compatible with many studies on BSG-based edible lms [50,51]. When the spectra were examined, it was observed that the O-H stretch bands became sharper and shifted to lower wave numbers with increasing glycerol concentration.…”
Section: Ft-ir Spectroscopysupporting
confidence: 84%
“…Mucilage contains polymers such as CH 2 , O-H, C-H, C-O-C, and the carboxylate group was observed in different studies. It was also observed that the spectra obtained from mucilage showed a huge peak value at the range of 3500-3300 cm −1 , the absorption band at around 3000-2800 cm −1 , 1270-1080 cm −1 , at 1600 cm −1 , and 1400 cm −1 confirming the vibrational stretching of the polymeric O-H group, CH 2 and C-H group, C-O group, Carboxylate asymmetric stretching, and symmetric stretching respectively [51][52][53]. Naji-Tabasi et al [54] conducted a study on basil seed mucilage, the FTIR analysis of the study indicated the existence of uronic acids, absorptions at wavelengths 1600 and 1400 cm −1 confirmed the presence of uronic acid assigned to C-OO asymmetrical and symmetrical stretching, respectively.…”
Section: Characterization Of the Mucilagementioning
confidence: 62%
“…The presence of crosslinked pectin in seed mucilage is well established in the literature (da Silveira Ramos et al, 2021; Kurd et al, 2017; Thessrimuang and Prachayawarakorn, 2019). The FTIR spectra for BSM and CSM along with low and high methoxy pectin for comparison are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 90%